Food for all in Africa: Sustainable intensification for African farmers - Conway, Gordon; Badiane, Ousmane; Glatzel, Katrin (Cornell University Press, 2019)
Foreword (pp. xiii-xiv) Acknowledgments (pp. xv-xvi) List of Acronyms (pp. xvii-xx) Introduction: A BOOK FOR OPTIMISTS (pp. 1-8) Part 1 CHALLENGES AND OPPORTUNITIES 1 AFRICAN FARMS AND FARMERS (pp. 11-31) 2 HUNGER AND MALNUTRITION (pp. 32-60) 3 THE THREATS TO FOOD SECURITY (pp. 61-84) 4 RESILIENT FARMERS (pp. 85-104) Part 2 SUSTAINABLE INTENSIFICATION 5 SUSTAINABLE AGRICULTURE (pp. 107-129) 6 AGRICULTURE AND ECOLOGY (pp. 130-156) 7 THE NEW GENETICS (pp. 157-187) 8 VALUE CHAINS (pp. 188-218) Part 3 AGRICULTURAL TRANSFORMATION 9 DIGITAL FARMERS (pp. 221-238) 10 TRANSFORMING AGRICULTURE (pp. 239-257) 11 LEADERSHIP AND PERFORMANCE (pp. 258-280)